Regulation of the Packaging of Bacillus thuringiensis δ-Endotoxins into Inclusions - Chang, Lily (American Society for Microbiology, 2001)
During sporulation, many Bacillus thuringiensis subspecies synthesize several related δ-endotoxins which are packaged into bipyramidal intracellular inclusions. These inclusions are solubilized in the alkaline, reducing conditions of the midguts of susceptible insect larvae and are converted by proteolysis to active toxins. The toxins insert into the membranes of cells lining the midgut and form cation-selective channels, which results in lethality. There are three δ-endotoxins, Cry1Ab3, Cry1Ca1, and Cry1Da1, present in the inclusions produced by a B. thuringiensis subsp. aizawai cell. While the ratio of the steady-state mRNAs for these three protoxins has been shown to differ (cry1Ab3/cry1Ca1/cry1Da1 mRNA ratio, 4:2:1), the half-lives of the cry1Da1 and cry1Ab3 mRNAs were found to be similar, indicating that there were differences in the transcription rates. The relative contents of these δ-endotoxins in purified inclusions from B. thuringiensis subsp. aizawai have been measured previously, and an even greater relative deficiency of the Cry1Da1 protoxin (ratio, 20:12:1) was found. In order to account for this deficiency, other steps which could be involved in inclusion formation, such as translation and packaging, were examined. The three cry genes have the same dual overlapping promoters, but the ribosome binding sequence for the cry1Da1 gene was not the consensus sequence. Translation was enhanced about fourfold by changing to the consensus sequence. In addition, the relative amount of Cry1Da1 protoxin in inclusions was twofold lower when cells were sporulated in Luria-Bertani (LB) medium than when cells were sporulated in a glucose-yeast extract medium. This difference was attributable to packaging since the relative amounts of Cry1Da1 antigen in cells sporulating in the two media were the same. Some factor(s) required for packaging of the Cry1Da1 protoxin in inclusions is apparently limiting in LB medium. Differences in the initial transcription rates, translation efficiencies, and packaging all contribute to the δ-endotoxin composition of an inclusion.